Heparanase as a potential player in SARS-CoV-2 infection and induced coagulopathy. Issue 7 (30th July 2021) - Kinaneh, Safa; Khamaysi, Iyad; Karram, Tony; Hamoud, Shadi
Abstract: During the current formidable COVID-19 pandemic, it is appealing to address ideas that may invoke therapeutic interventions. Clotting disorders are well recognized in patients infected with severe acute respiratory syndrome (SARS) caused by a novel coronavirus (SARS-CoV-2), which lead to severe complications that worsen the prognosis in these subjects. Increasing evidence implicate Heparan sulfate proteoglycans (HSPGs) and Heparanase in various diseases and pathologies, including hypercoagulability states. Moreover, HSPGs and Heparanase are involved in several viral infections, in which they enhance cell entry and release of the viruses. Herein we discuss the molecular involvement of HSPGs and heparanase in SARS-CoV-2 infection, namely cell entry and release, and the accompanied coagulopathy complications, which assumedly could be blocked by heparanase inhibitors such as Heparin and Pixatimod.